First detection of bovine noroviruses and detection of bovine coronavirus in Australian dairy cattle. Issue 6 (June 2018) - Symes, SJ; Allen, JL; Mansell, PD; Woodward, KL; Bailey, KE; Gilkerson, JR; Browning, GF
Abstract : Background and objective: Noroviruses have been recognised as a significant cause of neonatal enteritis in calves in many countries, but there has been no investigation of their occurrence in Australian cattle. This study aimed to establish whether bovine noroviruses could be detected in faecal samples from Australian dairy cattle. It also sought to determine whether bovine coronaviruses, also associated with neonatal enteritis in calves, could be detected in the same faecal samples. Methods: A selection of faecal samples that were negative for rotaviruses from dairy farms located in three geographically distinct regions of Victoria were pooled and tested by reverse transcription‐PCR for the presence of noroviruses (genogroup III), neboviruses and bovine coronaviruses. Results and conclusion: Genetically distinct genogroup III noroviruses were detected in two sample pools from different geographic regions and bovine coronavirus was detected in a third pool of samples. This is the first report of bovine norovirus infection in Australian cattle and suggests that future work is required to determine the significance of these agents as a cause of bovine enteric disease in Australia.